Seals and codes of good sustainable practices in the audiovisual industry: An approach to the state of the question - Blas Blas, Julio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The SDGs mark the path of companies towards sustainability. But we do not know if audiovisual, film and television companies are on the same path. In addition, there are some seals and codes of good practice that try to put sustainability in the shoot. This research tries to explain the oldest and most important initiatives on green filming: Green Production Guide and Albert. We analyse if they focus sustainability on the carbon footprint or also on social and governance actions, the three axes of sustainability. The results give a series of similarities in the processes, in the internal certification and in the interest in training; as well as differences in some areas of application and in social and governance matters.